Early Mobilization pada Ibu Post Pospartum Mempercepat Penyembuhan Luka Sectio Ceserea di RSUD dr Doris Sylvanus: Early Mobilization in Post Posartum Mothers Accelates the Healing of Sectio Ceserea Wounds in RSUD dr Doris Sylvanus - Yeni Lucin; Helinadiyaningsih Herlinadiyaningsih (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
inhibits the wound healing process, causing morbidity and mortality. Postoperative care is needed to prevent complications in the cesarean section. The first treatment that must be done after surgery is early mobilization and proper wound dressing. Early mobilization motivates the patient to move the feet and legs as soon as possible within 24 hours, leading to improved circulation, stimulating gastrointestinal function to return to normal. Objective: To determine the effectiveness of Early Mobilization in postpartum mothers on wound healing after Sectio Ceserea. This type of research is quasi-experimental with a Posttest Only Control Group Design. Purposive sampling technique. Samples of postpartum mothers with Sectio Ceserea post were 30 respondents in the intervention group, 30 control respondents, data analysis with the chi square test. The results of statistical tests showed that after the Early ambulance intervention in the treatment group the wound healing results were 100%. The relationship between early ambulation and wound healing in the treatment group was statistically significant (p<0.05). The external variable of clinical anemia (Risk Ratio) was 1.72. Primipara parity Risk Ratio 2.22 . Risk Ratio Grande result 2.07. Early Mobilization in postpartum mothers after Sectio Cesarea surgery is effective in accelerating wound drying